Survival rates of ultra‐short (<6 mm) compared with short locking‐taper implants supporting single crowns in posterior areas: A 5‐year retrospective study. (18th November 2021) - Lombardo, Giorgio; Signoriello, Annarita; Marincola, Mauro; Liboni, Pietro; Bonfante, Estevam A.; Nocini, Pier F.
Abstract: Background: Short and ultra‐short implants represent a predictable treatment, in terms of implant survival, with patients presenting insufficient available bone volumes. Moreover, single crown restorations represent a gold standard in terms of oral hygiene. Purpose: The aim of this retrospective study was to evaluate implant survival, marginal bone loss, and peri‐implant complications in 333 locking‐taper short and ultra‐short implants. Materials and Methods: Implants were placed in the maxillary and mandibular posterior regions of 142 patients. Clinical and radiographic examinations were performed at 5‐year recall appointments. Results: All implants placed consisted of 8.0‐, 6.0‐, and 5.0‐mm length, 38.14%, 34.53%, and 27.33%, respectively. Three hundred thirty‐two implants (one early failure) were rehabilitated with single crowns in 141 patients. In 45.48% of the implants the crown‐to‐implant ratio was ≥2, with a mean value of 1.94. Overall implant‐based survival after 5 years of follow‐up was 96.10%: 96.85%, 95.65%, and 95.60% for 8.0‐, 6.0‐, and 5.0‐mm length implants, respectively ( p  = 0.82). Overall patient‐based survival was 91.55%. Regarding crestal bone level variations, average crestal bone loss and apical shift of the "first bone‐to‐implant contact point" position were 0.69 and 0.01 mm, respectively. Setting the threshold for excessive bone loss at 1 mm, during the time interval from loading to follow‐up, 28 implants experienced loss of supporting bone greater than 1 mm: 19 of them (67.85%) were surgically treated with a codified surgical regenerative protocol. After 60 months, a peri‐implantitis prevalence of 5.94% was reported, with an overall implant success of 94.06%: 95.93%, 92.73%, and 93.10% for 8.0‐, 6.0‐, and 5.0‐mm length implants, respectively ( p  = 0.55). Conclusion: Long‐term outcomes suggest that short and ultra‐short locking‐taper implants can be successfully restored with single crowns in the posterior area of the maxilla and mandible.